Exploring NUP62’s role in cancer progression, tumor immunity, and treatment response: insights from multi-omics analysis - Chen, Lihong; He, Youfu; Duan, Menghui; Yang, Tianwen; Chen, Yin; Wang, Bo; Cui, Dejun; Li, Chen (Frontiers in Immunology, 2025)
BackgroundNUP62, a key component of the nuclear pore complex, is closely associated with cellular functions and cancer progression. However, its expression patterns, prognostic value, and relationship with tumour immunity and drug sensitivity across multiple cancers have not been systematically studied. This study used multi-omics analyses combined with experimental validation in gastric cancer to investigate the expression, functional characteristics, and clinical relevance of NUP62 in cancer.MethodsData from TCGA, GTEx, and CPTAC databases were used to analyse the expression, mutation characteristics, and clinical associations of NUP62. Tools such as SangerBox, TIMER 2.0, and GSEA were employed to evaluate the relationship between NUP62 and the tumour immune microenvironment, as well as its involvement in signalling pathways. Immunohistochemistry and RT-PCR were used to validate the expression of NUP62 in gastric cancer tissues. PRISM and CTRP databases were utilised to assess the correlation between NUP62 expression and drug sensitivity.ResultsNUP62 was significantly upregulated in multiple cancers and was associated with poor prognosis in cancers such as clear cell renal carcinoma (KIRC), lower-grade glioma (LGG), and adrenocortical carcinoma (ACC), while playing a protective role in others, such as bladder cancer (BLCA) and stomach cancer (STAD). Functional analyses showed that NUP62 is involved in cell cycle regulation, DNA damage repair, and tumour immunity. High NUP62 expression was significantly correlated with increased infiltration of immune cells, such as macrophages and T cells, and a higher response rate to immunotherapy. Drug sensitivity analysis identified NUP62 as a marker of sensitivity to various chemotherapeutic agents. Validation experiments demonstrated that NUP62 mRNA and protein levels were significantly higher in gastric cancer tissues than in adjacent normal tissues.ConclusionsNUP62 plays a critical role in multiple cancers and shows potential as a biomarker for cancer diagnosis, prognosis, and therapeutic response prediction. Its role in tumour immunity and signalling pathways highlights its potential as a target for immunotherapy and precision medicine.